Study on the Creep and Fracture Evolution Mechanism of Rock Mass with Weak Interlayers - Na Zhao; Yibin Zhang; Haibin Miao; Lixin Meng (Advances in Materials Science and Engineering)
To study the influence of weak interlayers on the creep failure characteristics of rock masses, based on the continuous-discontinuous method (CDEM), the uniaxial compression creep experiments of rock masses containing weak layers were numerically simulated; and the weakened rock masses under different conditions were analyzed in detail. We focused on the final failure mode and creep curve of the rock mass with a weak interlayer (θ = 30°, d = 20 mm, c = 1) as examples by selecting the crack distribution state of the model during compression at different time steps. We analyzed the propagation and convergence mode of cracks in a rock mass with weak layers. The research results show that the existence of weak interlayers affects the integrity of the rock mass and the creep failure mode. With the increase in the inclination of the weak interlayer, the failure mode of the rock mass changes from shear failure through the weak layer to slip along the weak layer. For shear failure, the total strain and steady-state creep rate of the rock mass first decrease and then increase, showing a U-shaped distribution; as the thickness of the weak interlayer increases, the rock mass always follows the shear in the weak layer. Creep failure occurs on the fracture surface, and the total strain and steady-state creep rate of the rock mass are positively correlated with the thickness. If the thickness continues to increase, there is no significant difference in the creep characteristics of the rock mass; the volume occupied by the soft rock in the body increases, the overall rigidity of the rock mass decreases, and the plastic deformation increases. The form of creep failure of the rock mass changes from sliding shear failure along the weak layer to sliding shear failure through the weak interlayer. The total strain and steady-state creep rate of the rock mass increase with the increase in the number of weak layers; the greater the distance between the weak layers, the smaller the total strain and steady-state creep rate of the rock mass. The slower the crack growth rate, the less likely the rock mass to undergo creep damage.